1970
DOI: 10.1029/wr006i003p00845
|View full text |Cite
|
Sign up to set email alerts
|

Dissolved Solids‐Discharge Relationships: 1. Mixing Models

Abstract: With the increasing interest in the relationships between dissolved constituents and discharge in streams a reasonable basis is needed for the selection of possible models that might aid in analyzing the data. A series of simple mixing models based on mass balance calculations is presented along with derivations and solutions for certain assumptions about the mixing volumes and the storage volume-discharge relationship. If concentration and discharge data show a hysteresis or loop relationship with time, then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0
1

Year Published

1978
1978
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(64 citation statements)
references
References 5 publications
(2 reference statements)
0
61
0
1
Order By: Relevance
“…from a smaller data set and used to estimate the fractional contribution of these constituents to the total nitrogen load. Hall [1970]. It assumes mixing of precipitation or event water with baseflow in an open stream system.…”
Section: Discussionmentioning
confidence: 99%
“…from a smaller data set and used to estimate the fractional contribution of these constituents to the total nitrogen load. Hall [1970]. It assumes mixing of precipitation or event water with baseflow in an open stream system.…”
Section: Discussionmentioning
confidence: 99%
“…Hystereses in the concentration-flow relationships are often observed during storm events, i.e. the concentration of a determinand, at a given river flow, is different on the rising and falling limb of a hydrograph (Hall, 1970). When plotted, such concentration/flow relationships result in ''loop trajectories'', with a clockwise hysteresis loop produced when the concentration is higher on the rising limb of the hydrograph, and an anticlockwise loop when the concentration is higher on the falling limb.…”
Section: Characterisation Of Hysteresis Trajectoriesmentioning
confidence: 99%
“…Typical concentration-discharge analyses have centered on mixing models of different source waters (e.g. event and pre-event water; old and new water; or soil water, groundwater and precipitation) inferred from the shape of the concentration-discharge relationship for different solutes (Johnson et al, 1969;Hall, 1970Hall, , 1971. In other studies, researchers have inferred the relative timing of mixing from hysteresis loops observed in concentration-discharge plots (Evans and Davies, 1998;Evans et al, 1999;House and Warwick, 1998;Hornberger et al, 2001;Chanat et al, 2002).…”
Section: Introductionmentioning
confidence: 99%